IDENTIFIKASI POTENSI PENGEMBANGAN PERTANIAN BERKAWASAN AGROWISATA DI KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Hauris, Hauris (Universitas Nahdlatul Ulama Pasuruan, 2024)
The development agrotourism in accordance with ecological characteristics and functions in any agricultural development will have direct effect on the preservation of land resources, farmers' income and increased welfare. This study aims to determine the potential for the development of agricultural sector with agrotourism area and the type area for agrotourism development. Determination of the research location was carried out purposively on the basis; location selection is very affordable, accessibility to arrive at location is relatively easy and administratively close to Palu City as the capital city of Central Sulawesi Province. Research respondents include; tanantovea subdistrict heads, community leaders, hamlet heads, women leaders, religious leaders, youth leaders and local communities know the potential developing agrotourism. Data analysis used descriptive analysis, which a method that examines and compares the actual problems that occur where its implementation preceded by presurvey, data collection process, the compilation explanations and analysis process aims to make a systematic, factual and accurate description of the research results. based on empirical facts, characteristics and relationships between phenomena studied. The results study explained that the identification of agricultural development potential in the area ​​agrotourism the Tanantovea sub-district, one of which is food crops and horticulture (fruits and vegetables) in Nupabomba village, tourism forest (botanical garden) in Nupabomba village, waterfalls in Wani village, onion business development. Fry in the villages of Guntarano and Wombo, and the development type agrotourism area is carried out through clear and planned study stages with the following stages: preparation of agrotourism area, pre-agrotourism area, and agrotourism area stage.